Pengaruh Kompensasi dan Motivasi Terhadap Kinerja Karyawan UMKM Rumah Makan - Aldo A (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this study was to determine the effect of compensation on employee performance and to determine the effect of motivation on employee performance. Types and sources of data The data used in this research is quantitative data or basic research type. This data is in the form of numbers or made into numbers. Based on the source, the data in this study are primary data obtained directly from the respondents. The conclusion that can be obtained from testing using SPSS is that compensation and work motivation have positive results or have a significant effect on employee performance. thus supporting the existing hypothesis, namely: the compensation variable (X1) has an influence on the performance variable (Y) and the motivational variable (X2) has an influence on the performance variable (Y).